Electroceramic glaze structure with composite transition layer and preparation method thereof

Through the gradient transition layer design and dynamic spraying process, the problem of easy cracking of the electric porcelain glaze when alternating between hot and cold is solved, multifunctionality and efficient production are achieved, and the strength and durability of the electric porcelain glaze are improved.

CN120622960AActive Publication Date: 2025-09-12HUNAN SUN POWER ELECTRIC PORCELAIN APPLIANCE MFG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510741775.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-09-12
Estimated Expiration
2045-06-05

AI Technical Summary

Technical Problem

Traditional electrical porcelain glazes are prone to cracking when subjected to alternating hot and cold temperatures, and have a single function. Existing technologies are difficult to simultaneously meet the complex requirements of antibacterial, conductive, or corrosion-resistant properties. Furthermore, the process is complex and costly, making it difficult to achieve industrial application.

Method used

By adopting gradient transition layer design and dynamic spraying process, by introducing base slurry, reinforcing agent and functional additives into the electric porcelain glaze, a continuously changing thermal expansion coefficient gradient is formed, combined with stabilizer doping to improve the strength and durability of the glaze.

Benefits of technology

It improves the bonding strength and thermal shock resistance of the electric porcelain glaze, solves the problem of easy cracking of the glaze, and at the same time realizes the multifunctional requirements and improves production efficiency and precision.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622960A_ABST
    Figure CN120622960A_ABST
Patent Text Reader

Abstract

The invention discloses an electric porcelain glaze structure with a composite transition layer and a preparation method of the electric porcelain glaze structure. The electric porcelain glaze structure sequentially comprises a bottom layer glaze, the transition layer and a surface layer glaze from a green body to the outside, the transition layer comprises matrix slurry and a reinforcing agent; the matrix slurry comprises # imgabs 1 # with the mass percent of # imgabs 0 # and silica sol with the mass percent of # imgabs 2 #; the reinforcing agent comprises nano # imgabs 4 # with the mass percent of # imgabs 3 #, # imgabs 6 # with the mass percent of # imgabs 5 # and nano # imgabs 8 # with the mass percent of # imgabs 7 #; the content of # imgabs9 is uniformly and progressively increased in the transition layer along the direction from the bottom layer glaze to the surface layer glaze, so that the transition layer forms a continuously changing CTE gradient; the content of the nano # imgabs10 # is uniformly and progressively decreased in the transition layer along the direction from the bottom layer glaze to the surface layer glaze, so that the excessive nano # imgabs11 # is prevented from reacting with the surface layer glaze components; the content of # imgabs12 is uniformly and progressively increased in the transition layer in the direction from the bottom layer glaze to the surface layer glaze so as to meet the high-temperature requirement of the surface layer glaze; the content of the nano # imgabs13 # is uniformly and progressively increased in the transition layer along the direction from the bottom layer glaze to the surface layer glaze so as to cope with the high thermal stress of the surface layer glaze.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric porcelain manufacturing, in particular to an electric porcelain glaze structure with a composite transition layer and a preparation method thereof. Background Art

[0002] The surface of electrical porcelain is usually covered with a layer of glaze to improve durability, but in traditional electrical porcelain structures, these glazes usually have certain defects. That is, when the electrical porcelain experiences alternating hot and cold, the glaze layer and the body expand and contract at different rates, and are prone to cracking at the junction. To improve toughness, traditional methods will add some other materials to the glaze to balance the thermal expansion coefficient, but these materials are unevenly distributed and may cause internal microcracks.

[0003] The glaze functions of existing electrical porcelain are relatively single and cannot simultaneously meet the complex requirements of antibacterial, conductive or corrosion resistance. Although existing technologies attempt to improve them by superimposing multiple layers of glaze or uniformly doping functional materials, these methods are usually complex and costly, or have limited performance improvements due to unreasonable material distribution, making them difficult to achieve industrial application. Summary of the Invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an electric porcelain glaze structure with a composite transition layer and a preparation method thereof, which improves the strength and durability of the electric porcelain glaze through innovative gradient transition layer design and dynamic spraying process.

[0005] In order to achieve the above-mentioned object, the present invention provides an electric porcelain glaze structure with a composite transition layer. In the technical solution of the present invention, the electric porcelain glaze structure includes a bottom glaze, a transition layer and a surface glaze in order from the body outward;

[0006] The transition layer includes a matrix slurry and a reinforcing agent, wherein the matrix slurry includes a mass percentage of of And the mass percentage is The reinforcing agent includes a mass percentage of Nano , mass percentage is of Rare earth oxides and mass percentages Nano .

[0007] Furthermore, in the technical solution of the present invention, the By doping with stabilizers, the The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , so that the transition layer forms a continuously changing CTE gradient; the nano The content in the transition layer decreases evenly from the bottom glaze to the surface glaze. Decrease evenly to , avoid excessive nano Reacts with ingredients in the top glaze; The content of rare earth oxides in the transition layer increases uniformly from the bottom glaze to the surface glaze. Increase evenly to , to match the higher temperature requirements of the surface glaze side; the nano The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , to cope with the higher thermal stress on the surface glaze side.

[0008] Furthermore, in the technical solution of the present invention, the bottom glaze adopts the following composition formula in mass percentage: of , of , of and of .

[0009] Furthermore, in the technical solution of the present invention, the surface glaze adopts the following composition formula in mass percentage: of , of , of , of as well as functional additives.

[0010] Furthermore, in the technical solution of the present invention, By doping with a stabilizer, the molar percentage of the stabilizer is of .

[0011] Furthermore, in the technical solution of the present invention, By doping with a stabilizer, the mass percentage of the stabilizer is of .

[0012] Furthermore, in the technical solution of the present invention, the functional additive is a nano Particles, nanoparticles particles and graphene.

[0013] Another aspect of the present invention provides a method for preparing an electrical porcelain glaze structure having a composite transition layer, which is used to realize the electrical porcelain glaze structure having a composite transition layer as described above, and specifically comprises the following steps:

[0014] Step S1, raw material pretreatment:

[0015] Step S1-1: Mix the base glaze formula raw materials and ball grind them until Making a bottom glaze slurry;

[0016] Step S1-2: doping The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and a reinforcing agent is added to prepare a transition layer slurry;

[0017] Step S1-3: Mix the raw materials of the surface glaze formula and ball grind them until preparing a surface glaze slurry;

[0018] Step S2, dynamic gradient spraying;

[0019] Step S2-1: Use wet electrostatic spraying process to spray the bottom glaze slurry on the blank with a spraying thickness of After spraying, pre-sintering is carried out at a temperature of 600°C for 30 minutes;

[0020] Step S2-2: Use a dual-channel dynamic spraying process to spray the transition layer slurry onto the bottom glaze with a spraying thickness of After spraying, perform infrared drying at a temperature of 80°C and a humidity of 50% RH for 10 minutes;

[0021] Step S2-3: Use the dipping method to attach the surface glaze slurry to the transition layer. The thickness of the surface glaze attached to the transition layer is After the dipping is completed, the temperature is 40-60 ° C, the humidity is 50% RH, and the time is 4-6 hours;

[0022] Step S3: Segmented sintering:

[0023] Step S3-1: After the dynamic gradient spraying is completed and the drying is completed, a first low-temperature pre-sintering is performed at a temperature of 800° C. for 1 hour;

[0024] Step S3-2: After the first stage of low-temperature pre-sintering, the temperature is rapidly raised to 1100°C for the second stage of transition sintering, and the firing time is 30 minutes;

[0025] Step S3-3: After the second stage of transition sintering, the temperature is further raised to 1250-1300°C for the third stage of high-temperature sintering for 20 minutes;

[0026] Step S3-4: After the third stage of high-temperature sintering is completed, the temperature is naturally lowered to 800° C., and then cooled to room temperature by air cooling.

[0027] Furthermore, in the technical solution of the present invention, in step S1-2, the doped The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and the transition layer slurry made by adding a reinforcing agent is divided into two categories:

[0028] Transition layer slurry type A: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is ;

[0029] Transition layer slurry type B: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is .

[0030] Furthermore, in the technical solution of the present invention, in step S2-2, the specific steps of spraying the transition layer slurry onto the bottom glaze using a dual-channel dynamic spraying process are as follows:

[0031] The dual channels are transition layer slurry type A and transition layer slurry type B;

[0032] The flow rate ratio of transition layer slurry type A and transition layer slurry type B during spraying is determined by Evenly change to .

[0033] Beneficial effects: In summary, the present invention provides an electric porcelain glaze structure with a composite transition layer and a preparation method thereof. In the technical solution of the present invention, the strength and durability of the electric porcelain glaze are improved through the innovative gradient transition layer design and dynamic spraying process. The content increases evenly from the bottom glaze to the surface glaze, which makes the thermal expansion coefficient between layers transition perfectly, can improve the bonding strength and thermal shock resistance of the electric porcelain glaze, and solve the problem of easy cracking of the traditional glaze; at the same time, in the technical solution of the present invention, the transition layer adopts a dual-channel dynamic spraying process, and through real-time regulation of different slurry ratios, it can form a composition gradient layer at one time, compared with the coating and drying process in the traditional process, it can effectively improve production efficiency and precision.

[0034] Other features and advantages of the present invention will be set forth in the description that follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0036] Figure 1 The present invention is a flowchart of a method for preparing an electrical porcelain glaze structure with a composite transition layer according to an embodiment of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, features, and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] The core of the embodiment of the present invention is to provide an electric porcelain glaze structure with a composite transition layer and a preparation method thereof, which improves the strength and durability of the electric porcelain glaze through an innovative gradient transition layer design and a dynamic spraying process.

[0039] On one hand, an embodiment of the present invention provides an electric porcelain glaze structure with a composite transition layer. In this embodiment, the electric porcelain glaze structure includes a bottom glaze, a transition layer and a surface glaze in sequence from the body outward.

[0040] Among them, the bottom glaze adopts the following composition formula by mass percentage: of , of , of and of .

[0041] Among them, the surface glaze adopts the following composition formula by mass percentage: of , of , of , of as well as functional additives.

[0042] The transition layer includes a matrix slurry and a reinforcing agent, and the matrix slurry includes a mass percentage of of And the mass percentage is of silica sol, At high temperatures, the tetragonal phase to monoclinic phase transformation occurs, which can absorb the crack propagation energy and improve the thermal shock resistance of the glaze layer; the reinforcing agent includes a mass percentage of Nano , mass percentage is of Rare earth oxides and mass percentages Nano , add nano Can be used with Forming a "nanocomposite structure" to inhibit Abnormal grain growth, while passing Bond strengthens the bond with the base glaze, adding Rare earth oxides can be sintered with generate Glassy phase, filled grain boundaries, reducing interfacial energy and improving high-temperature oxidation resistance.

[0043] Specifically, in this embodiment, By doping with stabilizers, The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , so that the CTE gradually changes between layers during sintering, so that the transition layer forms a continuously changing CTE gradient; nano The content in the transition layer decreases evenly from the bottom glaze to the surface glaze. Decrease evenly to , avoid excessive nano With the surface glaze The ingredients react; The content of rare earth oxides in the transition layer increases uniformly from the bottom glaze to the surface glaze. Increase evenly to , to match the higher temperature requirements of the surface glaze side; nano The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , to cope with the higher thermal stress on the surface glaze side.

[0044] Specifically, in this embodiment, By doping with a stabilizer, the molar percentage of the stabilizer is of .

[0045] In another embodiment, By doping with a stabilizer, the mass percentage of the stabilizer is of .

[0046] Specifically, in this embodiment, the functional additive is nano Particles, nanoparticles particles and graphene.

[0047] On the other hand, this embodiment also provides a method for preparing an electric porcelain glaze structure with a composite transition layer, which is used to realize the electric porcelain glaze structure with a composite transition layer as described above. Figure 1 FIG. 1 is a flow chart of a method for preparing an electrical porcelain glaze structure with a composite transition layer according to this embodiment. Figure 1 As shown, the specific steps include:

[0048] Step S1, raw material pretreatment:

[0049] Step S1-1: Mix the base glaze formula raw materials and ball grind them until Making a bottom glaze slurry;

[0050] Step S1-2: doping The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and a reinforcing agent is added to prepare a transition layer slurry;

[0051] Step S1-3: Mix the raw materials of the surface glaze formula and ball grind them until preparing a surface glaze slurry;

[0052] Step S2, dynamic gradient spraying;

[0053] Step S2-1: Use wet electrostatic spraying process to spray the bottom glaze slurry on the blank with a spraying thickness of After spraying, pre-sintering is performed at a temperature of 600°C for 30 minutes to remove organic matter and preliminarily sinter the neck connection;

[0054] Step S2-2: Use a dual-channel dynamic spraying process to spray the transition layer slurry onto the bottom glaze with a spraying thickness of After spraying, perform infrared drying at a temperature of 80°C and a humidity of 50% RH for 10 minutes to prevent cracking;

[0055] Step S2-3: Use the dipping method to attach the surface glaze slurry to the transition layer. The thickness of the surface glaze attached to the transition layer is After impregnation, dry the mixture at a temperature of 40-60°C and a humidity of 50% RH for 4-6 hours to avoid rapid shrinkage and cracking.

[0056] Step S3: Segmented sintering:

[0057] Step S3-1: After the dynamic gradient spraying and drying are completed, a first low-temperature pre-burning is performed at a temperature of 800°C (heating rate of 5°C / min) for 1 hour to slowly remove residual moisture and volatile gases;

[0058] Step S3-2: After the first stage of low temperature pre-sintering, the temperature is quickly raised to 1100℃ (heating rate is 10℃ / min) for the second stage of transition sintering, and the firing time is 30 minutes. Abnormally large particles;

[0059] Step S3-3: After the second stage of transition sintering, the temperature is further raised to 1250-1300°C for the third stage of high-temperature sintering, which is carried out for 20 minutes to complete the sintering;

[0060] Step S3-4: After the third stage of high-temperature sintering is completed, the temperature is naturally lowered to 800° C., and then cooled to room temperature by air cooling.

[0061] Specifically, in this embodiment, in step S1-2, the doped The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and the transition layer slurry made by adding a reinforcing agent is divided into two categories:

[0062] Transition layer slurry type A: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is ;

[0063] Transition layer slurry type B: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is .

[0064] Specifically, in this embodiment, in step S2-2, the specific steps of spraying the transition layer slurry onto the bottom glaze using a dual-channel dynamic spraying process are as follows:

[0065] The dual channels are transition layer slurry type A and transition layer slurry type B;

[0066] The flow rate ratio of transition layer slurry type A and transition layer slurry type B during spraying is determined by Evenly change to .

[0067] The above shows and describes the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely preferred examples of the present invention and are not intended to limit the present invention. Various changes and improvements may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and improvements fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. An electrical porcelain glaze structure with a composite transition layer, characterized in that: From the body outward, it includes bottom glaze, transition layer and surface glaze; The transition layer comprises: The matrix slurry includes a mass percentage of of And the mass percentage is Silica sol; Reinforcement agent, including mass percentage Nano , mass percentage is of Rare earth oxides and mass percentages Nano ; described By doping with stabilizers, the The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , so that the transition layer forms a continuously changing CTE gradient; The nano The content in the transition layer decreases evenly from the bottom glaze to the surface glaze. Decrease evenly to , avoid excessive nano Reacts with ingredients in the top glaze; described The content of rare earth oxides in the transition layer increases uniformly from the bottom glaze to the surface glaze. Increase evenly to , to match the higher temperature requirements of the surface glaze side; The nano The content in the transition layer increases evenly from the bottom glaze to the surface glaze. Increase evenly to , to cope with the higher thermal stress on the surface glaze side.

2. The electrical porcelain glaze structure with a composite transition layer according to claim 1, characterized in that: The bottom glaze adopts the following composition formula by mass percentage: of , of , of and of .

3. The electrical porcelain glaze structure with a composite transition layer according to claim 1, characterized in that: The surface glaze adopts the following composition formula in mass percentage: of , of , of , of as well as functional additives.

4. The electrical porcelain glaze structure with a composite transition layer according to claim 1, characterized in that: In the By doping with a stabilizer, the molar percentage of the stabilizer is of .

5. The electrical porcelain glaze structure with a composite transition layer according to claim 1, characterized in that: In the By doping with a stabilizer, the mass percentage of the stabilizer is of .

6. The electrical porcelain glaze structure with a composite transition layer according to claim 3, characterized in that: The functional additive is nano Particles, nanoparticles particles and graphene.

7. A method for preparing an electrical porcelain glaze structure with a composite transition layer, for realizing an electrical porcelain glaze structure with a composite transition layer as claimed in any one of claims 1 to 6, characterized in that: The steps include: Step S1, raw material pretreatment: Step S1-1: Mix the base glaze formula raw materials and ball grind them until Making a bottom glaze slurry; Step S1-2: doping The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and a reinforcing agent is added to prepare a transition layer slurry; Step S1-3: Mix the raw materials of the surface glaze formula and ball grind them until preparing a surface glaze slurry; Step S2: dynamic gradient spraying: Step S2-1: Use wet electrostatic spraying process to spray the bottom glaze slurry on the blank with a spraying thickness of After spraying, pre-sintering is carried out at a temperature of 600°C for 30 minutes; Step S2-2: Use a dual-channel dynamic spraying process to spray the transition layer slurry onto the bottom glaze with a spraying thickness of After spraying, perform infrared drying at a temperature of 80°C and a humidity of 50% RH for 10 minutes; Step S2-3: Use the dipping method to attach the surface glaze slurry to the transition layer. The thickness of the surface glaze attached to the transition layer is After the dipping is completed, the temperature is 40-60 ° C, the humidity is 50% RH, and the time is 4-6 hours; Step S3: Segmented sintering: Step S3-1: After the dynamic gradient spraying is completed and the drying is completed, a first low-temperature pre-sintering is performed at a temperature of 800° C. for 1 hour; Step S3-2: After the first stage of low-temperature pre-sintering, the temperature is rapidly raised to 1100°C for the second stage of transition sintering, and the firing time is 30 minutes; Step S3-3: After the second stage of transition sintering, the temperature is further raised to 1250-1300°C for the third stage of high-temperature sintering for 20 minutes; Step S3-4: After the third stage of high-temperature sintering is completed, the temperature is naturally lowered to 800° C., and then cooled to room temperature by air cooling.

8. The method for preparing an electrical porcelain glaze structure with a composite transition layer according to claim 7, characterized in that: In the step S1-2, the doped The powder is mixed with silica sol, ultrasonically treated for 2-4 hours using an ultrasonic dispersion process, and the transition layer slurry made by adding a reinforcing agent is divided into two categories: Transition layer slurry type A: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is ; Transition layer slurry type B: The mass percentage is ,nanometer The mass percentage is , The mass percentage of rare earth oxides is ,nanometer The mass percentage is .

9. The method for preparing an electrical porcelain glaze structure with a composite transition layer according to claim 8, characterized in that: In step S2-2, the specific steps of spraying the transition layer slurry onto the bottom glaze using a dual-channel dynamic spraying process are as follows: In the dual channels, there are transition layer slurry type A and transition layer slurry type B respectively; The flow rate ratio of transition layer slurry type A and transition layer slurry type B during spraying is determined by Evenly change to .

Citation Information

Patent Citations

  • Gradient wiredrawing glaze and method for preparing gradient wiredrawing glaze ceramic product by using gradient wiredrawing glaze

    CN113248142A

  • ceramic INSULATOR.

    DE1711455U

  • Glaze composition for ceramics substrate

    JP1991164444A

  • Production of glazed ceramic base plate

    JP1993132382A

  • Partial conductive-glazed insulator

    JP1996264052A